Variables Selection Procedure for the DEA Overall Efficiency Assessment Based Plithogenic Sets and Mathematical Programming (International Journal of Scientific Research and Management (IJSRM), 2022)
The appropriate selection of inputs and outputs also their count is a crucial step to achieve relevant results for any study involving the measurement of a set of decision-making units’ overall efficiency using the data envelopment analysis methodology. In the literature, however, there is still no definitive standard to guide this selection. This article offers a novel two-phase procedure allowing, by solving an integer non-linear program in the first phase, to determine the most suitable number of both inputs and outputs to be used. And then, by following a developed plithogenic multi-criteria decision-making method in the second phase, to specify inputs and outputs that have the most contribution in improving efficiency and should be considered in the DEA model. A running example is applied throughout this article to make the proposed procedure more comprehensible. It consists in selecting variables for measuring the overall efficiency of the Northern Border University in Saudi Arabia. Obtained results consider at the same time the uncertainty aspect of data, also indeterminacy in experts’ judgments towards inputs and outputs.